Recombinant Porphyromonas gingivalis W83 FimA alters immune response and metabolic gene expression in oral squamous carcinoma cells - Sabine E. Groeger; Martina Hudel; Silke Zechel‐Gran; Jens M. Herrmann; Trinad Chakraborty; Eugen Domann; Joerg Meyle (Wiley, 2022)
Abstract Objectives The Gram‐negative anaerobic rod Porphyromonas gingivalis (P. gingivalis) is regarded as a keystone pathogen in periodontitis and expresses a multitude of virulence factors iincluding fimbriae that are enabling adherence to and invasion in cells and tissues. The progression of periodontitis is a consequence of the interaction between the host immune response and periodontal pathogens. The aim of this study was to investigate the genome‐wide impact of recombinant fimbrial protein FimA from P. gingivalis W83 on the gene expression of oral squamous carcinoma cells by transcriptome analysis. Materials and Methods Human squamous cell carcinoma cells (SCC‐25) were stimulated for 4 and 24 h with recombinant FimA. RNA sequencing was performed and differential gene expression and enrichment were analyzed using gene ontology (GO), Kyoto Encyclopedia of Genes and Genomes (KEGG), and REACTOME. The results of transcriptome analysis were validated using quantitative real‐time polymerase chain reaction (PCR) with selected genes. Results Differential gene expression after 4 and 24 h revealed upregulation of 464 (4 h) and 179 genes (24 h) and downregulation of 69 (4 h) and 312 (24 h) genes. GO, KEGG, and REACTONE enrichment analysis identified a strong immunologic transcriptomic response signature after 4 h. After 24 h, mainly those genes were regulated, which belonged to cell metabolic pathways and replication. Real‐time PCR of selected genes belonging to immune response and signaling demonstrated strong upregulation of CCL20, TNFAIP6, CXCL8, TNFAIP3, and NFkBIA after both stimulation times. Conclusions These data shed light on the RNA transcriptome of human oral squamous carcinoma epithelial cells following stimulation with P. gingivalis FimA and identify a strong immunological gene expression response to this virulence factor. The data provide a base for future studies of molecular and cellular interactions between P. gingivalis and oral epithelium to elucidate basic mechanisms that may provide new prospects for periodontitis therapy and give new insights into the development and possible treatments of cancer.